Stability and function of a putative microtubule-organizing center in the human parasite Toxoplasma gondii - Leung, Jacqueline M. (Mol Biol Cell, 2017)
The organization of the microtubule cytoskeleton is dictated by microtubule nucleators or organizing centers. Toxoplasma gondii, an important human parasite, has an array of 22 regularly spaced cortical microtubules stemming from a hypothesized organizing center, the apical polar ring. Here we examine the functions of the apical polar ring by characterizing two of its components, KinesinA and APR1, and show that its putative role in templating can be separated from its mechanical stability. Parasites that lack both KinesinA and APR1 (ΔkinesinAΔapr1) are capable of generating 22 cortical microtubules. However, the apical polar ring is fragmented in live ΔkinesinAΔapr1 parasites and is undetectable by electron microscopy after detergent extraction. Disintegration of the apical polar ring results in the detachment of groups of microtubules from the apical end of the parasite. These structural defects are linked to a diminished ability of the parasite to move and invade host cells, as well as decreased secretion of effectors important for these processes. Together the findings demonstrate the importance of the structural integrity of the apical polar ring and the microtubule array in the Toxoplasma lytic cycle, which is responsible for massive tissue destruction in acute toxoplasmosis.